Practical vs theoretical ethics: A response to Cox. Issue 1 (22nd January 2021) - Bailey, Jon S.
Abstract : In the recent article, "Descriptive and Normative Ethical Behavior Appear to be Functionally Distinct, " the case was presented for an analysis of ethical conduct based on the Western philosophical approach derived from descriptive and normative ethics (Cox, 2020). The author conducted two experiments with graduate students evaluating whether these two approaches were functionally related. Participants gave forced‐choice as well as free responses that were later hand‐coded. Cox concluded that descriptive and normative ethics are functionally distinct. A critique of this general approach is offered based on a concern that this approach may not be steering the field in a direction that is ultimately useful for practitioners or relevant in therapeutic settings. Suggestions for future directions for practical ethical research are offered which, we might hope, should provide us with a better understanding of the variables controlling ethical conduct in practical situations.